Brigas de família: tramas de sociabilidades no sertão do Ceará - Maia, Dália Maria Bezerra (2008)
This dissertation shows a reflection on family struggles in the sertão of Ceará. Comprehended as a particular type of conflict, these struggles are characterized by the use of physical violence for family groups (composed of individuals who may be or may not be connected by consanguinity) as a way of reaction to an affront and execution of vengeance. In the comprehension of this phenomenon, I tried to consider the family struggles not through a plenary or systemic vision, but from the social actors‘ point of view, which I tried to apprehend in my field research realized mainly in one of the municipalities located in the Valley of Jaguaribe River. I was interested in showing how people live, think and concede a sense to these experiences of conflict. I also tried to understand, through the narrative of these struggles, how these disputes interfere and sometimes help to shape the individuals‘ relations of sociability in that social universe.